Differential microRNA Expression in Newcastle Disease Virus-Infected HeLa Cells and Its Role in Regulating Virus Replication - Chen, Yu; Zhu, Shanshan; Pei, Yuru; Hu, Jiao; Hu, Zenglei; Liu, Xiaowen; Wang, Xiaoquan; Gu, Min; Hu, Shunlin; Liu, Xiufan (Frontiers in Oncology, 2021)
As an oncolytic virus, Newcastle disease virus (NDV) can specifically kill tumor cells and has been tested as an attractive oncolytic agent for cancer virotherapy. Virus infection can trigger the changes of the cellular microRNA (miRNA) expression profile, which can greatly influence viral replication and pathogenesis. However, the interplay between NDV replication and cellular miRNA expression in tumor cells is still largely unknown. In the present study, we compared the profiles of cellular miRNAs in uninfected and NDV-infected HeLa cells by small RNA deep sequencing. Here we report that NDV infection in HeLa cells significantly changed the levels of 40 miRNAs at 6 h post-infection (hpi) and 62 miRNAs at 12 hpi. Among 23 highly differentially expressed miRNAs, NDV infection greatly promoted the levels of 3 miRNAs and suppressed the levels of 20 miRNAs at both time points. These 23 miRNAs are predicted to target various genes involved in virus replication and antiviral immunity such as ErbB, Jak-STAT, NF-kB and RIG-I-like receptor. Verification of deep sequencing results by quantitative RT-PCR showed that 9 out of 10 randomly selected miRNAs chosen from this 23-miRNA pool were consistent with deep sequencing data, including 6 down-regulated and 3 up-regulated. Further functional research revealed that hsa-miR-4521, a constituent in this 23-miRNA pool, inhibited NDV replication in HeLa cells. Moreover, dual-luciferase and gene expression array uncovered that the member A of family with sequence similarity 129 (FAM129A) was directly targeted by hsa-miR-4521 and positively regulated NDV replication in HeLa cells, indicating that hsa-miR-4521 may regulate NDV replication via interaction with FAM129A. To our knowledge, this is the first report of the dynamic cellular miRNA expression profile in tumor cells after NDV infection and may provide a valuable basis for further investigation on the roles of miRNAs in NDV-mediated oncolysis.